2017
DOI: 10.1186/s12903-017-0344-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical registry of dental outcomes in head and neck cancer patients (OraRad): rationale, methods, and recruitment considerations

Abstract: BackgroundMost head and neck (H&N) cancer patients receive high-dose external beam radiation therapy (RT), often in combination with surgery and/or chemotherapy. Unfortunately, high-dose RT has significant adverse effects on the oral and maxillofacial tissues, some of which persist for the life of the patient. However, dental management of these patients is based largely on individual and expert opinion, as few studies have followed patients prospectively to determine factors that predict adverse oral sequelae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
(15 reference statements)
0
24
0
1
Order By: Relevance
“…10 The current study reports baseline dental findings and dental recommendations as of June 23, 2016. Also, data is reported for 5 of 6 enrollment sites because the sixth site, UNC, recently started enrollment and had only 1 participant enrolled at the time of this analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The current study reports baseline dental findings and dental recommendations as of June 23, 2016. Also, data is reported for 5 of 6 enrollment sites because the sixth site, UNC, recently started enrollment and had only 1 participant enrolled at the time of this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…10 The study received IRB approval at all enrollment sites. Consented participants are enrolled before they begin RT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it is of extreme importance that primary clinicians counsel patients after HNRT about oral and dental surveillance, including minimizing sugar intake, maintaining good oral hygiene and fluoride use, and keeping the dental care routine with a short interval between appointments (preferably every 3 months) so that any changes can be detected and treated in early stages. 23,24 Jackson et al, 25 in a recent attempt to develop an oral health evaluation tool for oral health outcomes in patients with HNC, also applied the ICDAS for dental assessment of patients after chemoradiation. They found that over 40% of the sample presented moderate-tosevere dental caries (ICDAS stages 5 and 6), corroborating our finding that the RRC lesions are predominately diagnosed in late stages.…”
Section: Discussionmentioning
confidence: 99%
“…Oral samples were not collected at 12 months post-RT, although the DMFS score data were available. A detailed description of methodology and an extensive overall description of the ORARAD study population regarding primary tumor site, oral hygiene and dental disease measures, and other oral complications have been previously reported [23][24][25].…”
Section: Patient Recruitmentmentioning
confidence: 99%